The Effect Of Marital Status On The Independence Of The Elderly In Fulfilling Activities Of Daily Living (ADL): A Systematic Review And Meta-Analysis - Masnarivan, Yeffi; Elfansdha Putri, Ezzha; Aulia Ramadhan, Fathiya; Fidela Lubis, Marsha; Akbari Affa, Sausan (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background : Indonesia's population projection in 2045 the population pyramid is estimated to be stationary with a greater contribution of the very old population. Creating independent elderly starts with basic independence in fulfilling activities of daily living (ADL) for the elderly. The purpose of this study was to see the effect of marital status on the independence of elderly ADLs. Method : The research study design used was a systematic review accompanied by a meta-analysis. Article search strategy through Pudmed electronic database and Google Schoolar. Data analysis using Refman 5.4.1. Result : Forest plot shows negative results where statistical analysis shows highly significant results (p < 0.00001, Heterogeneity (IÂ²) = 96% with effect size (d = 0.44) CI (0.32 to 0.60) which indicates heterogeneous data distribution (random effect). Asymmetrical funnel plot means there is potential bias. Conclusion : The results of the meta-analysis show that marital status has a significant influence on the independence of daily living activities of the elderly with a p-value <0.00001 effect size (d = 0.44) CI (0.32 to 0.60). Keywords: Marital Status; Elderly; Activities Of Daily Living